PREVENTION OF AUTONOMIC DISADAPTATION IN SERVICE MEMBERS - Kyrychenko, A.G.; Kornatsky, V.M.; Serdiuk, V.M.; Abramov, S.V.; Ogorenko, V.V. (World of Medicine and Biology, 2020)
The autonomic nervous system (ANS) is the main regulator of maintaining homeostasis and organism adaptation to changes in the environment. Most often, autonomic dysfunction occurs under the conditions of chronic psychoemotional stress. To prevent emotion dysregulation and stress-related disorders in service members, the state of the autonomic nervous system was assessed by examining 145 military servicemen, considering the initial autonomic tone, autonomic reactivity and autonomic support of the individual. In most subjects there was tension and dysfunction of the ANS, which allowed us to recommend a more thorough study of its three main components in order to identify autonomic disorders and the allocation of these persons to the risk group for psychosomatic pathology.